Resourceful ageing: Empowering older people to age resourcefully with the Internet of Things - Giaccardi, Elisa; Nicenboim, Iohanna (2023)
In products designed specifically for older people, the inventiveness and resourcefulness of the elderly is often underestimated in favour of designs that overestimate the extent to which older people are in need of assistance. This book is about what older people can still do. The book describes an award-winning project that combined design experimentation, machine learning, and ethnographic fieldwork to create and prototype designs that could support older people in everyday practices of resourcefulness. The results offer the reader a categorized set of strategies for supporting resourcefulness in older people’s everyday lives; methodological considerations on algorithmic design practices and the role of machine learning in support of improvisation; and, relevant design tools and techniques. The book concludes with reflections on the importance of designing technology for older people not as ‘intervention’, but as ‘resources’. If designers want to support ageing in place, they must empower older people to configure technology with a higher degree of freedom. Editors: Elisa Giaccardi, Iohanna Nicenboim Authors: Elisa Giaccardi, Iohanna Nicenboim, Lenneke Kuijer, Louis Neven, Hayley Hung, Ivo Maathuis, Yanxia Zhang, Benjamin Lopez